The Role of Organizational Culture and Budget Participation in Enhancing Managerial Performance in Government: A Systematic Literature Review - Ranti Melasari; Sri Rahayu; Wirmie Eka Putra; Rita Friyani; Wiwik Tiswiyanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to systematically examine the relationship between budget participation and organizational culture on improving managerial performance in the government sector. Using the Systematic Literature Review (SLR) approach with PRISMA guidelines, a total of ten relevant national and international scientific articles in the period 2020 - 2025 were analyzed thematically and comparatively. The results showed that budget participation generally contributes positively to managerial performance, especially when supported by an adaptive, collaborative and inclusive organizational culture. Organizational culture plays an important role as a reinforcing factor, which can maximize the effectiveness of the participatory budgeting process. However, there were also variations in results that were influenced by organizational characteristics, leadership styles, and internal cultural readiness. This study concludes that the synergy between participatory systems and organizational culture is a key prerequisite for creating superior managerial performance in government environments. The findings provide strategic implications for policy makers in designing more participatory budget governance and building an organizational culture that supports bureaucratic transformation.